Feasibility of Imaging-Based Quantitative Hepatic Function Assessment: Gd-EOB-DTPA-Enhanced Liver MR Imaging Combined with T1 Mapping - Dong, Zhi; Wang, Meng; Feng, Yanqing; Cai, Huasong; Feng, Shi-Ting; Li, Zi-Ping; Lin, Zhi; Peng, Zhenpeng (Current Medical Imaging, 2023)
Objective: to investigate the feasibility of gadoxetic acid (Gd-EOB-DTPA) enhanced MRI combined with T1 mapping in quantitative hepatic function assessment. Methods: this study retrospectively enrolled 94 patients with Gd-EOB-DTPA enhanced MRI combined with T1 mapping, divided into group A (grade A, n=73), group B (grade B, n=14) and group C (grade C, n=7) based on Child-Pugh classification. Liver T1 relaxation times on plain scan (T1P) and hepatocellular phase (T1E) were measured. Decrease in T1 (T1D) and the percentage of decrease in T1 (T1D%) were calculated as follows: T1D=T1P-T1E, T1D%= T1D/T1P×100%. The relationship between T1P, T1E, T1D, T1D% and liver function classification was analyzed. Results: T1P, T1D, and T1D% in group A were significantly higher than those of group B and C. T1E in group A was lower than those of group B and C. T1D% was significantly different between group B and C. There was no significant difference in T1P, T1E, T1D between groups B and C. T1E was positively correlated with liver function levels, T1P and T1D had a negative correlation with liver function levels. T1P, T1E, T1D, T1D% were significantly different between cirrhotic and non-cirrhotic groups. T1D% of less than 70% suggests liver dysfunction. Conclusion: Gd-EOB-DTPA enhanced liver MRI combined with T1 mapping is feasible for quantitative assessment of hepatic function.
Keywords: Gadoxetic acid